2019
DOI: 10.1021/acs.iecr.9b03512
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Hydrate Dissociation Curves in the Presence of Hydrate Inhibitors with a Modified CPA EoS

Abstract: A modified CPA equation of state has been applied for the description of noninhibited hydrates. In this work, this model is applied to the description of dissociation curves of hydrates inhibited by six thermodynamic inhibitors (methanol, ethanol, MEG, DEG, TEG, and glycerol), while also focusing on promoting a correct simultaneous description of SLE and VLE between the inhibitors and water. The study concern some of the most well-known hydrate formers (methane, ethane, propane, CO 2 , Xe, and H 2 S) and mixtu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…21 An overview of the accuracy of this model, as used in this work, to represent hydrate dissociation curves for many common hydrate formers with and without inhibitors is available from the literature. 6,7 The effect of salts on the solubility of gases and gas hydrate formation was modeled using the Debye−Huckel theory, virial corrections, and Born terms. The basic principle of the electrolyte model applied to this study is similar to many published models that can be found in the literature.…”
Section: Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…21 An overview of the accuracy of this model, as used in this work, to represent hydrate dissociation curves for many common hydrate formers with and without inhibitors is available from the literature. 6,7 The effect of salts on the solubility of gases and gas hydrate formation was modeled using the Debye−Huckel theory, virial corrections, and Born terms. The basic principle of the electrolyte model applied to this study is similar to many published models that can be found in the literature.…”
Section: Modelsmentioning
confidence: 99%
“…Hydrates were modeled with the solid solution theory of Platteeuw and van der Waals, as developed by Parrish and Prausnitz . An overview of the accuracy of this model, as used in this work, to represent hydrate dissociation curves for many common hydrate formers with and without inhibitors is available from the literature. , …”
Section: Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The generated dataset can be arbitrarily large and the data itself is noise-free as it is generated by a thermodynamically consistent method such as the solids thermodynamic model implemented in the HydraFLASH software that is integrated into Prosper. For a given acid gas mixture, HydraFLASH uses the multiphase equilibrium algorithm by Michelsen [50], the van der Waals and Platteeuw theory and the CPA EoS [51] to predict the hydrate dissociation curve for the acid gas mixture of interest.…”
Section: Classification Models Inputmentioning
confidence: 99%